Impacts of logging disturbance on soil dynamics and fungal communities in Cherul Forest Reserve, Terengganu - Azrai, Suzazsuzuludin; Patahayah, Mansor; Ahmad Syazwan, Samsuddin; Sahira-Aimaa, Khairi Nur; Dahali, Rasdianah; Hishamuddin, Muhammad Syahmi (Elsevier B.V., 2025)
Tropical forests are biodiversity hotspots where fungal communities play a central role in nutrient cycling, plant symbiosis, and ecosystem resilience. However, selective logging poses a significant threat to these below-ground microbial assemblages. This study investigates the impact of logging intensity on fungal community structure, and functional composition in the Cherul Forest Reserve, Terengganu, Malaysia. Using high-throughput sequencing of environmental DNA from soil samples collected across a gradient of disturbance, namely virgin forest (VF), regeneration forest (RF), and logged-over forest (LF), we analysed changes in fungal alpha diversity, beta diversity, taxonomic composition, and functional guild distribution. Results revealed that RF harboured the highest fungal diversity, while LF exhibited marked declines, with VF showing intermediate values. Ascomycota and Russulaceae dominated across all sites, although Basidiomycota, particularly ectomycorrhizal fungi (ECMF), were more abundant in VF, indicating their sensitivity to disturbance. Saprotrophic and pathogenic fungi, such as Hypocreaceae and Trichocomaceae, were more prevalent in disturbed forests, suggesting functional shifts toward opportunistic decomposers and pathogens. Non-metric multidimensional scaling and PERMANOVA revealed no statistically significant differences in overall community composition among forest types, but functional guild-specific patterns were apparent. Soil chemical properties, including pH, nitrogen, and phosphorus availability, significantly differed across sites and were correlated with fungal shifts. Multivariate ordination (CCA and RDA) showed that topsoil guilds were most strongly associated with pH, phosphorus, and nitrogen, while subsoil guilds were influenced by magnesium and carbon, highlighting depth-dependent soil–fungi relationships. These findings underscore the ecological ramifications of logging on soil fungal communities, with implications for forest regeneration and carbon dynamics. Our study highlights the importance of preserving fungal diversity and incorporating soil microbial indicators into sustainable forest management practices to support ecosystem recovery and long-term resilience in tropical forests.